PEMODELAN KEAUSAN KONTAK Sliding ANTARA SILINDER DENGAN BIDANG DATAR - I. Syafa’at; Jamari -; S.A. Widyanto; R. Ismail (Universitas Muhammadiyah Semarang, 2010)
Telah lama para peneliti mempelajari keausan yang terjadi karena kontak dua buah benda, baik secara analitik dan numeris untuk menganalisa secara tepat dalam komponen permesinan. Paper ini membahas tentang pemodelan keausan silinder pada bidang datar menggunakan pendekatan analitik dan simulasi elemen hingga. Pemodelan keausan dikembangkan dari model Hegadekatte untuk kasus line contact secara analitik. Dengan updated geometry dari simulasi software ANSYS, nilai tegangan maksimal yang diperoleh, digunakan untuk menghitung keausan Archard. Hasil kajian ini menunjukkan model analitik dan simulasi elemen hingga memiliki hasil yang bagus.Over the years, many researchers have conducted some studies analytically and numerically dealing with wear on two contacting surfaces due to its important in reliability analysis on mechanical components. This paper presents analytical and numerical wear modeling of sliding contact between a cylinder against flat. The development of Hegadekatte’s analytical model for line contact is obtained to model the wear of the cylinder. The updating geometry is used in finite element software, ANSYS to predict the geometry change of the cylinder due to wear. The prediction is made by using the contact pressure, resulted from finite element simulation as an input in Archard wear equation. The comparison between the analytical and finite element simulation result performs good agreement.Kata kunci: kontak sliding, keausan, silinder